Freedom of expression and the times of emergency: analysis of Article 15 of the European Convention on Human Rights and derogations made by Turkey and Hungary during COVID-19 pandemic - Lazdāne, Alīna (Riga Graduate School of Law, 2021)
COVID-19 pandemic is regarded not to be solely a health crisis, but also human rights crisis. The pandemic limited freedom of movement, freedom of expression, right to education, food security, and other rights. The thesis focuses on the limitation to the freedom of expression in Europe under the ECHR framework during the COVID-19 pandemic in Turkey and Hungary. In Europe, there are more than one hundred alerts on the limitation to the freedom of expression during the pandemic. The thesis is to provide an in-depth understanding and analysis of the derogation procedure of the ECHR under Article 15 ECHR and the limitation procedure to the freedom of expression under Article 10(2) ECHR. Based on the interpretation of the derogation and limitation clause, introduced Coronavirus bill and the amendments to the Criminal Code to criminalise spread of untrue facts or misinterpreted true facts in Hungary and amendments to the Social Media Law in Turkey are to be analysed
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Freedom of speech; Turkey; Hungary